The effects of brief online self-help intervention strategies on emotions and satisfaction with running performance - Lane, A.; Devonport, T.; Stanley, D.; Beedie, C. (Sensoria - A journal of mind, brain and culture, 2016)
The present study investigated the effects of online self-help interventions on emotions and satisfaction with performance in a sample of runners (N = 147). Participants set themselves a running time goal they wished to achieve, and made goal attempts pre and post-intervention. After the first goal attempt, participants were randomly assigned to 1 of 3 groups: (1) implementation intentions (if-then planning), (2) goal setting, and (3) control group. During both goal attempts, participants reported the intensity of pre-run emotions retrospectively and satisfaction with performance. Results indicated post-intervention emotions were significantly more pleasant and less unpleasant, with more runners reported as performing to expectation. Results also indicated emotion-performance satisfaction relationships strengthened post-intervention. Contrary to expectations, implementation intentions did not produce greater benefits when compared to goal-setting intervention and control groups. We suggest that future research should continue to investigate the efficacy of brief online interventions in regulating emotions and performance.